Microbiota engraftment after faecal microbiota transplantation in obese subjects with type 2 diabetes: a 24-week, double-blind, randomised controlled trial. Issue 4 (30th March 2021) - Ng, Siew C; Xu, Zhilu; Mak, Joyce Wing Yan; Yang, Keli; Liu, Qin; Zuo, Tao; Tang, Whitney; Lau, Louis; Lui, Rashid N; Wong, Sunny H; Tse, Yee Kit; Li, Amy Y L; et al.
Abstract : Objective: The impact of faecal microbiota transplantation (FMT) on microbiota engraftment in patients with metabolic syndrome is uncertain. We aimed to study whether combining FMT with lifestyle modification could enhance the engraftment of favourable microbiota in obese patients with type 2 diabetes mellitus (T2DM). Design: In this double-blind, randomised, placebo-controlled trial, 61 obese subjects with T2DM were randomly assigned to three parallel groups: FMT plus lifestyle intervention (LSI), FMT alone, or sham transplantation plus LSI every 4 weeks for up to week 12. FMT solution was prepared from six healthy lean donors. Faecal metagenomic sequencing was performed at baseline, weeks 4, 16 and 24. The primary outcome was the proportion of subjects acquiring ≥20% of microbiota from lean donors at week 24. Results: Proportions of subjects acquiring ≥20% of lean-associated microbiota at week 24 were 100%, 88.2% and 22% in the FMT plus LSI, FMT alone, and sham plus LSI groups, respectively (p<0.0001). Repeated FMTs significantly increased the engraftment of lean-associated microbiota (p<0.05). FMT with or without LSI increased butyrate-producing bacteria. Combining LSI and FMT led to increase in Bifidobacterium and Lactobacillus compared with FMT alone (p<0.05). FMT plus LSI group had reduced total and low-density lipoprotein cholesterol and liver stiffness at week 24 compared with baseline (p<0.05). Conclusion: Repeated FMTs enhance the level and duration of microbiota engraftment in obese patients with T2DM. Combining lifestyle intervention with FMT led to more favourable changes in recipients' microbiota and improvement in lipid profile and liver stiffness. Trial registration number: NCT03127696 .